The role of MVP strategy in increasing company competitiveness in a fast-paced environment - Ivanova, O.; Berest, K. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2024)
This article explores the importance of the Minimum Viable Product (MVP) strategy in enhancing the competitiveness of IT companies. The MVP strategy allows businesses to develop a simplified product version with only essential features, enabling faster time-to-market, real-world testing, and feedback gathering. This approach minimizes development risks, optimizes resource use, and helps companies move iteratively, through gradual testing of their hypotheses. By launching a lean product, companies can gain a first-mover advantage and to gain a foothold in the market faster. The article defines MVP as a minimal, functional representation of a product designed to test business hypotheses through customer feedback. This article also distinguishes MVPs from prototypes, which focus on testing functionality, and fully-fledged products, which are complete versions ready for commercial release. Through strategic market validation, MVPs allow companies to identify user needs early on and refine their offerings accordingly. The study also discusses the transition from MVPs to achieving economies of scale. As demand grows, companies can spread fixed costs over an increasing number of units, thereby reducing unit cost and increasing profitability. MVP strategy allows companies to focus on the essential product features and avoid spreading their resources on potentially unprofitable items, which contributes to efficient scaling. Case studies, such as that of Aardvark, illustrate how businesses can efficiently scale their MVPs into fully developed products. While the MVP strategy provides significant advantages, the article highlights potential downsides, such as underdeveloped products, biased user feedback and technical debt. Thus, while MVPs offer a valuable framework for growth and competitiveness, companies must apply them carefully, maintaining a balance between the possibility of short-term release accelerations and long-term scalability.